2012
DOI: 10.1007/978-1-61779-536-7_24
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging and Evaluation of Spines in Organotypic Hippocampal Slice Cultures

Abstract: Dendritic spines act as sites of excitatory neuronal input in many types of neurons. Spine shape correlates with the strength and maturity of synaptic contacts. Thus, evaluation of spine morphology is relevant for studies on neuronal development, for determination of morphological correlates of learning and memory, and for analysis of mechanisms of neurodegeneration. Here, we describe a method to determine spine morphology in an ex vivo model of organotypic hippocampal slice cultures prepared from transgenic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The method employed confocal high-resolution imaging of fixed slices followed by algorithm-based image analysis with the program 3DMA neuron. We and others had previously shown that this approach allows sensitive and robust evaluation of dendritic spines (Santuccione et al, 2013; Sundermann et al, 2012; Tackenberg et al, 2013). We observed that the density of spines was reduced in most regions and time points in APP SDL transgenic cultures compared to control cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method employed confocal high-resolution imaging of fixed slices followed by algorithm-based image analysis with the program 3DMA neuron. We and others had previously shown that this approach allows sensitive and robust evaluation of dendritic spines (Santuccione et al, 2013; Sundermann et al, 2012; Tackenberg et al, 2013). We observed that the density of spines was reduced in most regions and time points in APP SDL transgenic cultures compared to control cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In short, one or two week old APP SDL transgenic or non-transgenic C57BL/6 mice were decapitated, brains were removed, both hippocampi isolated and cut into 400 μm thick slices using McIllwain tissue chopper (Gabler, Bad Schwalbach, Germany). Slices were cultured as described previously (Sundermann et al, 2012; Tackenberg and Brandt, 2009). On day 12 or day 17 in vitro slice cultures were infected with Sindbis virus using droplet method (Shahani et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal slice cultures were prepared from mice of either sex and processed as described previously [ 5 , 52 ]. On day 12 in vitro slice cultures were infected with Sindbis virus.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging of the dissociated cells was performed after 24 h of EGFP expression (Malinow et al, 2010). In organotypic hippocampal slice culture, virus infection was performed as described previously (Sündermann et al, 2012). Briefly, 12 DIV slices were infected with the pSinRep5 EGFP virus following the droplet method.…”
Section: Sindbis Virus Infectionmentioning
confidence: 99%